Evaluating the effect of sowing date and drought stress on morphological and functional characteristics of three genotypes of winter oilseed rape (Brassica napus L.) - Seyyed Hamid REZA RAMAZANI; Reza TAHERPOUR KALANTARI (Acta Agriculturae Slovenica)
To assess the effects of drought stress and sowing date on phenological, morphological, and yield traits of three different cultivars of winter oilseed rape (Brassica napus L.), this study was conducted in research farm of Sarayan agricultural college- University of Birjand in 2016-2017 growing season. Experiment was conducted in a split-factorial based on the randomized complete block design with drought stress in the main plots and three sowing date (September 22, October 6, and October 22) along with three cultivars of canola (‘Homolious’, ‘Hayola50’, and ‘DK7070CL’) in the subplots in three replications. The results of analysis of variance and means comparison analysis showed significant and negative effect of drought stress on seed yield and biological yield traits of investigated cultivars of canola. The interaction effect of drought stress × sowing date × cultivar was only significant on leaf twisting trait at 1 % probability level. ‘Homolious’ was assigned as the most drought tolerance cultivar, based on SI, SSI, RDI, TOL, MP, STI, GMP, YI, YSI, and HARM drought tolerance indexes, whereas ‘Hayola50’ was assigned as most drought sensitive cultivar of oilseed rape.